Stalk-derived carbon dots as nanosensors for Fe3+ ions detection and biological cell imaging - Du, Yongchao; Li, Yaxi; Liu, Yunliang; Liu, Naiyun; Cheng, Yuanyuan; Shi, Qiuzhong; Liu, Xiang; Tao, Zhimin; Guo, Yumeng; Zhang, Jianguo; Askaria, Najmeh; Li, Haitao (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Iron is one of the most important needed elements for the growth and reproduction of living organisms. The detection of iron levels is important and developing fluorescent probes with excellent sensitivity for Fe3+ ions is of great significance. Carbon dot (CDs) is a new type of fluorescent nanomaterial based on abundant and low-cost carbon elements. The use of widely distributed renewable agricultural waste straw as a carbon precursor to prepare CDs sensor can not only reduce the pollution caused by burning straw to the atmospheric environment, but also achieve the transformation of resources from waste to treasure. Methods: In this study, CDs were obtained from corn stalk powder by pyrolysis and microwave process. The sensitivity and linear response range of CDs sensor was studied through analyzing the effect of different Fe3+ ions concentrations on the fluorescence quenching. The application of CDs in biological cell imaging was investigated using HGC-27 cells. Results: The fluorescence quenching showed a good linear relationship with the Fe3+ concentration in the range from 0 to 128 μM, and a low detection limit of 63 nM. In addition, the CDs have high recognition for Fe3+ ions. Meanwhile, the CDs have a low cytotoxicity and desirable biocompatibility, allowing the multicolor living cell imaging. Conclusion: The prepared CDs can be used as fluorescent sensors for the selective detection of Fe3+ ions and biological cell imaging. Our results supported that the conversion of agricultural waste into carbon nanomaterials has great potential to be developed.